2016
DOI: 10.3141/2577-02
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Calcium Nitrate for Concrete Applications

Abstract: The use of encapsulating healing agents that allow the self-healing of concrete has emerged as a potential solution to the current decay and costly maintenance of concrete infrastructure; however, many healing agents are expensive. The objectives of this study were to develop a procedure for the production of urea–formaldehyde microcapsules of calcium nitrate and to evaluate the effects of the microcapsules on self-healing efficiency in concrete. Calcium nitrate was selected for microencapsulation, given its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Interestingly, as the capsule concentration increased, the air content decreased. This trend differs from what has been reported with polymeric capsules (such as urea-formaldehyde), where larger amounts of capsules yielded higher air contents ( 29 ). This difference can be attributed to the encapsulation process, where polymeric capsules require surfactants that tend to increase the air content within the cement paste, while the calcium alginate beads were prepared without surfactants.…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, as the capsule concentration increased, the air content decreased. This trend differs from what has been reported with polymeric capsules (such as urea-formaldehyde), where larger amounts of capsules yielded higher air contents ( 29 ). This difference can be attributed to the encapsulation process, where polymeric capsules require surfactants that tend to increase the air content within the cement paste, while the calcium alginate beads were prepared without surfactants.…”
Section: Resultscontrasting
confidence: 99%
“…In other words, the strength recovery was greatly enhanced on the specimens with the higher amount of microcapsules. Similar findings have been found in other studies confirming the positive impacts of the micro-encapsulated healing agents on the mechanical performance after undergoing a healing scheme [43,48,[50][51][52]72]. Sidiq et al [41] found that crack width up to 122 µm was effectively healed with embedded microcapsules containing sodium silicate and the crack healing ratio achieved up to 60%.…”
Section: Self-healing Propertiessupporting
confidence: 82%
“…In general, thin-walled microcapsules would fail during the production process and concrete mixing, while thick-walled microcapsules are reluctant to break as the propagated crack will hardly penetrate [17]. The morphology, size and shape of prepared microcapsules are dependent on numerous factors including temperature, pH and agitation rate [17,18,42,43].…”
Section: Novel Self-healing Agentsmentioning
confidence: 99%
“…Hassan et al developed a synthesis for production of ureaformaldehyde microencapsulation of calcium nitrate (9). The authors evaluated the self-healing efficiency in concrete as the modulus of elasticity increased after healing on all specimens containing microcapsules.…”
Section: Objectives and Scopementioning
confidence: 99%